Analysis of the Readability of Questionnaires on Symptoms of Pelvic Floor Dysfunctions Adapted to Spanish. - Checa-Moreno, Víctor; Díaz-Mohedo, Esther; Suárez-Serrano, Carmen (MDPI, 2021)
Questionnaires are tools of interest in the evaluation of pelvic floor dysfunctions, but their success depends on their readability. Evaluating symptoms associated with such dysfunctions through questionnaires validated in Spanish with adequate readability indices will be useful for subsequent therapeutic work with these patients. The objective of this study is to evaluate the readability of symptomatology questionnaires on pelvic floor dysfunctions adapted to Spanish. This descriptive study included a total of 19 questionnaires, whose readability was analyzed according to four indices: Fernández-Huerta, Szigriszt-Pazos, Inflesz and readability µ (mu). In total, 50% of the questionnaires for fecal incontinence symptoms were found to have inadequate scores in terms of readability, according to the Inflesz index. If we take the readability mu index as a reference, the number of questionnaires that do not meet the minimum readability limit are as follows: 20% in urinary incontinence, 50% in fecal incontinence, 66.6% in sexual function, 100% in general pelvic floor, 25% in overactive bladder and 100% in benign prostatic hyperplasia. Therefore, it is necessary to review and adapt health questionnaires on pelvic floor dysfunctions to improve their readability and ease of understanding by conducting studies with the people who fill out these questionnaires.
Keywords: Suelo pélvico - Disfunción; Incontinencia urinaria; Incontinencia fecal; Vejiga hiperactiva; Hiperplasia benigna de próstata; Salud - Cuestionarios; Benign prostatic hyperplasia; Fecal incontinence; Overactive bladder; Pelvic floor dysfunctions; Questionnaire; Urinary incontinence